Feasibility Study of a 200 kWp Solar PV System for Residential Camps in Remote Locations: Case Study of Ndawara Tea Estate, Cameroon - Yvan Ayuketah; Wirnkar Basil Nsanyuy (Energy Science & Engineering)
ABSTRACT This study evaluates the feasibility of designing and implementing a 200 kWp solar photovoltaic (PV) system for the residential camp at Ndawara Tea Estate, Cameroon. The study aims to provide a sustainable and reliable power supply for workers and their families living in remote locations with limited grid access. Using PVSyst software, the system was designed, sized, and simulated to assess its technical and economic viability. The results indicate that a 200 kWp fixed‐tilted grid‐connected solar PV system can generate 389 MWh of electricity annually at a levelized cost of energy of 0.0715 USD/kWh, which is lower than average household electricity tariffs in Cameroon. The system also achieves an average performance ratio (PR) of 84.7%, with strong financial indicators supporting its viability. While results may differ for other plantation communities due to site‐specific conditions, Cameroon's high solar irradiation makes solar PV generation a practical and effective solution. The study concludes that solar PV systems can provide sustainable and affordable electricity for plantation communities, improving energy access, and reducing reliance on costly and unreliable power sources.